A 5 GHz CMOS tunable image-rejection low noise amplifier - Lee, Ler Chun (2006)

(untitled)
A 5 GHz image-rejection low-noise amplifier (IR-LNA) was designed using Silterra's CMOS 0.18 Âµm RF process. The IR-LNA employs a tunable third-order notch filter to reject the image signal. The notch filter was designed using a metal-insulator-metal capacitor (MTM) and a high quality factor (Q) active resonator. The notch frequency of the filter can be tuned using active inductor. The IR-LNA was simulated using HSPICE with BSIM3v3 MOSFET models. Simulation results show that the IR-LNA exhibits S11 of-22.67 dB, S21 of 16.45 dB, S12 of-75.84 dB, 2.66 dB noise figure (NF), and -21.8 dBm input compression point (P1dB) at 5 GHz. The power dissipation of the IR-LNA is 15.46 mW. With an intermediate frequency of 550 MHz, the image-rejection of the notch filter is -16dB. The tuning range of the notch filter is from 3.30 GHz to 4.15 GHz with a maximum -36 dB image rejection.